COVID-19 and cause of pregnancy loss during the pandemic: A systematic review - Kazemi, Seyyedeh Neda; Hajikhani, Bahareh; Didar, Hamidreza; Hosseini, Sareh Sadat; Haddadi, Sara; Khalili, Farima; Mirsaeidi, Mehdi; Nasiri, Mohammad Javad (PloS one, 2021)
Introduction The association between Coronavirus Disease 2019 (COVID-19) and abortion has been debated since the beginning of the COVID-19 pandemic. We aimed to conduct this systematic review to understand better the potential effects of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) on fetal loss in infected mothers presented with abortion following this infection. Methods We included articles published in PubMed/Medline, Web of Science, clinicaltrials.gov, and Embase databases in 2019 and 2020 through a comprehensive search via appropriate keywords, including COVID-19 and abortion synonyms. All studies with the abortion data in COVID-19 confirmed pregnant females were collected. Results Out of 208 potentially relevant articles, 11 articles were eligible to include in the systematic review. The included reports were published because of the following reasons: (1) First-trimester miscarriage; (2) Late miscarriage; (3) complication of COVID-19 infection in pregnancy; (4) COVID-19 disease in artificial pregnancy. First-trimester abortion was found in 5 studies, and second-trimester abortion in 7 studies. Two patients acquired infection during the hospital stay while they were referred for abortion. Reports related to abortion in pregnant females with COVID-19 show that most miscarriages due to COVID-19 in the first trimester were due to placental insufficiency. Conclusions There is an increased risk of abortion in mothers with a positive test result of SARS-CoV-2, which several case reports and case series have identified during the pandemic. Placental inflammation during the viral infection may result in fetal growth retardation and induce abortion. There has not been any consistent evidence of vertical transmission of the virus from mother to fetus, which requires further investigation.